Insight into phagocytosis of mature sexual (gametocyte) stages of Plasmodium falciparum using a human monocyte cell line - Bansal, Geetha P. (Acta Trop, 2016)
During natural infection malaria parasites are injected into the bloodstream of a human host by the bite of an infected female Anopheles mosquito. Both asexual and mature sexual stages of Plasmodium circulate in the blood. Asexual forms are responsible for clinical malaria while sexual stages are responsible for continued transmission via the mosquitoes. Immune responses generated against various life cycle stages of the parasite have important roles in resistance to malaria and in reducing malaria transmission. Phagocytosis of free merozoites and erythrocytic asexual stages has been well studied, but very little is known about similar phagocytic clearance of mature sexual stages, which are critical for transmission. We evaluated phagocytic uptake of mature sexual (gametocyte) stage parasites by a human monocyte cell line in the absence of immune sera. We found that intact mature stages do not undergo phagocytosis, unless they are either killed or freed from erythrocytes. In view of this observation, we propose that the inability of mature gametocytes to be phagocytized may actually result in malaria transmission advantage. On the other hand, mature gametocytes that are not transmitted to mosquitoes during infection will eventually die and undergo phagocytosis, initiating immune responses that may have transmission blocking potential. A better understanding of early phagocytic clearance and immune responses to gametocytes may identify additional targets for transmission blocking strategies.